Horlicks / Johny Jelliance Clement ... [et al.] - Clement, Johny Jelliance; Kudang, Christina; Tajuddin, Fauziah; Japar, Nur Izzaty; Heren, Veneta (2016)
Horlicks is a type of milk-based drinks hot malt which was founded by two British born siblings, William Horlick (184 6 - 1936) and his brother James (1844 - 1921) from Gloucestershire, England. Horlicks has been marketed and manufactured by GlaxoSmithKline which is Consumer Healthcare in the United Kingdom, South Africa, Pakistan, India, and Jamaica and under license in the Philippines and Malaysia. In addition, James is a chemist and has worked in a company that produces dry food for babies. William Horlick, the younger brother James also had immigrated to America in 1869. In 1873, James has decided to join his brother in Chicago. And in the same year, they started their own company, namely ( J & W Horlicks ) to make malted drinks. James and William Horlick have called their product as "Diastroid" as well as their advertising slogan of "Horlicks Infant and Invalids Food". In addition, the basic ingredient for horlicks is such as malted barley, wheat flour and evaporated milk. The good things is that nowadays, horlicks is available in many flavors including original, chocolate, banana, and also strawberry. In year 1875, James and William Horlicks moved to Racine, Wisconsin because they have to move to a bigger place to promote their products. Therefore, their new factory is a small one-storey wooden building with seven windows on each side. Next, on June 5, year 1883, William Horlick and James has given a total of 278 967 patents and the first malted milk patent for their ability to mix malted beverage powder with the hot water. Then, in 1890, James has returned to London to set up offices there and manage to import their products from the United States. In 1906 , a very large demand from the United Kingdom to allow horlicks set up their own factories there. While in 1908 completed construction of its first factory United Kingdom in Slough, Barkshire and baron was made by James in 1914. Then, late in 1921, James died and the company was divided into two and it was given the responsibility to James son for all over the world except in America because in America, William continue to manage their companies there. In 1930, Horlicks has dropped from the product description phrase ''malted" and in 1935 it was opened in Australia horlicks to supply Australia and New Zealand. Later, in 1936, William died faithful; he is ninety years old and British company horlicks buys out American horlick in year 1945.Futhermore, in 1955, horlicks powder has been exported to India for bottling and sealing. However, the basic protection of the government in India ceased imported for Horlicks in the same year. Next, on 30 October 1958, the factory opened in Nabha, Punjab which is located in India and subsidiary called as “Hindustan Milk food Manufacturers Pvt.Ltd”. While in 1968, Horlicks factory was opened in Pakistan. And in year 1969, horlicks was sold to Beecham. Thereafter, the Horlicks mixture was added with calcium and protein in 1988. Lastly, in 1990, more than seventy per cent of Horlicks sold to people over forty five in the United Kingdom. In addition, the company has launched that appears younger as young people who drink it.